BURNETT, Henry. Nietzsche, Adorno e um pouquinho de Brasil. São Paulo: Editora Unifesp, 2011 - Garcia, André Luis Muniz; Peterlevitz, Mayra Closs (Revista de Filosofia Moderna e Contemporânea, 2016)
Resenha